Detection and identification of protein citrullination in complex biological systems. (February 2016) - Clancy, Kathleen W; Weerapana, Eranthie; Thompson, Paul R
Highlights: Protein citrullination is aberrantly upregulated in inflammatory disease and cancer. Citrullinated proteins serve as antigens for RA-associated autoantibodies. Citrullinated proteins will also likely serve as disease specific biomarkers. Citrullination results in a 1 Da mass increase that is challenging to identify by MS. Chemical probes are improving our ability to identify citrullinated residues. Abstract : Protein citrullination is a post-translational modification of arginine that is catalyzed by the Protein Arginine Deiminase (PAD) family of enzymes. Aberrantly increased citrullination is associated with a host of inflammatory diseases and cancer and PAD inhibitors have shown remarkable efficacy in a range of diseases including rheumatoid arthritis, lupus, atherosclerosis, and ulcerative colitis. In rheumatoid arthritis, citrullinated proteins serve as key antigens for rheumatoid arthritis-associated autoantibodies. These data suggest that citrullinated proteins may serve more generally as biomarkers of specific disease states, however, the identification of citrullinated residues remains challenging due to the small 1 Da mass change that occurs upon citrullination. Herein, we highlight the available techniques to identify citrullinated proteins/residues focusing on advanced MS techniques as well as chemical derivatization strategies that are currently being employed to identify citrullinated proteins as well as the specific residues modified within those proteins.